THE CONTRIBUTION OF EDUCATION AND TEACHING EXPERIENCE TO THE PROFESSIONALISM OF SDLB TEACHERS - Wahyu Kurniawan; Su’ad Su’ad; Sukirman Sukirman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Teachers of Special Schools (SLB) are demanded to have professionalism in teaching. The teachers’ professionalism represents the commitment of teachers to improve their professional abilities and to develop their skills in carrying out their duties and functions as teachers. This study aimed to determine the effect of education, training, and teaching experience on teachers’ professionalism of special elementary school (SDLB) teachers in Kabupaten Kudus. This study was an explanatory research with a quantitative approach. The research subjects were 63 SDLB teachers in Kabupaten Kudus. The samples were selected through total sampling technique. The data were collected through a questionnaire and were analzed by using multiple regression analysis. The results showed that education partially had a positive and significant effect on the professionalism of SDLB teachers in Kabupaten Kudus. Similarly, teaching experience partially gave a positive and significant effect on the professionalism of SDLB teachers in Kabupaten Kudus. Overall, this study found that both education and teaching experience had a positive and significant effect on the professionalism of SDLB teachers. This was supported by the result of the coefficient of determination (R2) of 0.645 showing that the influence of education and teaching experience on teacher professionalism was 64.5%. moreover, teaching experience had the greatest influence on teachers’ professionalism for 55.4% while the effect of education was 9.1%. This study concluded that the professionalism of SDLB teachers in Kabupaten Kudus could be increased by providing more teaching experience and trainings as an effort to improve teachers’ competence